Spectrum and Infrastructure Sharing in Wireless Mobile Networks: Advantages and Risks - Bublin, Mugdim; Čaušević, Samir (Promet - Traffic&Transportation, 2008)
In recent time the spectrum and infrastructure sharing hasbeen gaining more and more on importance due to high spectrumlicense costs and expensive infrastructure needed formodem high-bandwidth wireless communications. In this paperthe advantages and disadvantages of spectrum and infrastructuresharing by analytical models and simulations are analyzed.Results show that operators could significantly reducetheir costs, increase capacity and improve network quality bysharing their infrastructure and spectrum. Using Game Theoryit is shown how operators could ’protect themselves’ againstnon-cooperative behaviour of other operators.